Uslub tasybih in Malay figurative language in the novel Suriati from fine arts approach - Kamarudin, Kamariah; Ishak, Nadia (Dewan Bahasa dan Pustaka, 2022)
One of the elements that liven up the storyline of a piece of work is uslub. Uslub or language style is the pulse that moves the process of writing. A language style that is not appropriate or ambiguous will affect the storyline. In studying a text with Islamic elements, it is important that the uslub of the text matches the content. The analysis of uslub is important in order to understand the message of a particular text. Therefore, this study analyses uslub tasybih, in the context of Malay figurative language from the novel Suriati (1993) written by Azizi Haji Abdullah from the Fine Arts Approach through the Religious Methodology contained in the Malay Methodology Theory (1989). This study uses the Malay Methodology as the analytical framework. It analyzes the relationship between uslub tasybih in the context of Malay Figurative Language and the literary work with Islamic elements in the novel Suriati. The focus of this study is to show whether the uslub tasybih in the context of Malay Figurative Language that were applied match the novel studied and reflect the aspects of Islamic beauty, thus conforming to the approach adopted in this study. The findings show that the uslub tasybih in the context of Malay Figurative Language have a direct relationship in Islamic literary work and highlight the Fine Arts Approach features which emphasize the aspect of beauty based on Islamic aesthetic values. Therefore, uslub tasybih should be in accordance with the requirements of Islam in the pursuit of perfection, civility, and order in all activities carried out by Muslims.